Extended-release metformin in patients with prediabetes, chronic heart failure and abdominal obesity in light of the effect on fat depot compartments and glucose metabolism parameters - O. V. Tsygankova; N. E. Apartseva; L. D. Latyntseva; A. N. Ryabikov (Сахарный диабет)
BACKGROUND: Considering the role of visceral adipose tissue deposition in the pathogenesis of heart failure with preserved ejection fraction (HFpEF) and the positive effect of metformin on weight loss, the effect of this drug on adipose tissue compartments in patients with HFpEF is interest.AIM: To study the effect of extended-release metformin (XR) on various fat depots and parameters of insulin-glucose homeostasis in patients with HFpEF, prediabetes and abdominal obesity (AO).MATERIALS AND METHODS: Study design: single-center, open-ended, randomized, prospective, controlled. The registration numbers of the study in the NARNIS register RNI.25.004. The study included 64 people (50% men, median age 58 [55.25; 59.75] years) with HFpEF, prediabetes and AO. All patients (groups A and B) received optimal HFpEF therapy. In group A (n=32), metformin XR 1000–1500 mg/day was additionally prescribed. All patients underwent general clinical examination, calculation of insulin resistance indices, ultrasound lipometry to determine the thickness of epicardial, preperitoneal and subcutaneous fat initially and after 6 months.RESULTS: In group A patients, there was a decrease in waist circumference by 0.9% (p=0.002), hip circumference by 1.25% (p=0.001), body weight by 4.7% (p<0.0001), body mass index by 1.8% (p=0.001) compared with baseline. In the control group, the anthropometric parameters of the dynamics did not change. Also, in the metformin XR group, glucose levels decreased by 4.6% (p=0.009), glycated hemoglobin by 3.3% (p=0.047), insulin by 12.5% (p=0.024) and insulin resistance indices: HOMA-IR by 19.8% (p=0.009), FIRI by 19.8% (p=0.009). In contrast, patients from group B had an increase in fasting plasma insulin levels by 33.6% (p=0.035), with an increase in HOMA-IR indices by 27.4% (p=0.026) and FIRI by 26.9% (p=0.025). The dynamics of ultrasound lipometry parameters was observed only in group A: the thickness of the preperitoneal fat decreased by 14.5% (p<0.0001), the thickness of the subcutaneous fat decreased by 12.3% (p<0.0001).CONCLUSION: In patients with prediabetes, HFpEF and AO, taking metformin XR 1000-1500 mg/day for 6 months against the background of optimal basic HFpEF therapy was associated with a decrease in subcutaneous and preperitoneal fat, also had a beneficial effect on glucose metabolism parameters compared with the control group.